Frequency of lumbosacral transitional vertebra and its relationship with disease related parameters of patients with axial spondyloarthritis - Serkan Sevindik; Kemal Erol; Funda Levendoğlu; Ilknur Albayrak Gezer (Journal of Rheumatic Diseases)
Objective: The aim of this study was to evaluate the prevelance of lumbosacral transitional vertebrae (LSTV) in patients with axial spondyloarthritis (ax-SpA), and to explore the relationship of the presence of LSTV with the burden of disease.Methods : : A total of 177 patients classified with ax-SpA according to ASAS (Assessment of Spondyloarthritis International Society) criteria who were admitted to Selçuk University Medical Faculty rheumatology outpatient clinic were included, consecutively. Demographic, clinical, and laboratory data were recorded. LSTV was evaluated on AnteroPosterior (AP) pelvic radiographs and AP lumbar radiographs according to the Castellvi classification.Results : : Of 177 patients with axSpA, 99 (55.9%) were radiographic axSpA (r-axSpA). LSTV was detected in 51 (28.8%) patients with ax-SpA (with the frequency of 32.3% in r-axSpA and 24.4% in non-r-axSpA [nr-axSpA] [p>0.05]). Most frequent LSTV subtype was type 1 (32 of 51 [62.7%]). Thirty-two (62.7%) of 51 patients with LSTV were r-axSpA, and 19 (37.3%) patients with LSTV were nr-axSpA (p=0.245). The demographic characteristics of the group with and without LSTV were similar. There was no significant difference in terms of VAS, BASDAI, BASFI, ASDAS-CRP, BASMI, HAQ, EQ-5D-3L scores and no difference in disease activity in terms of presence of LSTV in patients with ax-SpA.Conclusion : : The prevalence of LSTV in patients with ax-SpA was 28.8%, consistent with some population based studies in the literature. There was no difference between patients with and without LSTV in terms of burden of disease in patients with ax-SpA.